Screening of the variable levels of ascorbic acid concentration, temperature, and pH on extraction of crude pectin from caco pod husk. - Tocayon. Anthony C.; Icaldre, Rabin I., Velasco; Ma. Cailah Joyce D.
Cacao pod husks (CPH) make up most of the cacao fruit that are usually underutilized during the production of cacao-based products and contribute to existing ecological problems in the country. This warrants the investigation of CPH for other beneficial uses, such as a natural excipient for pharmaceutical dosage forms. The use of natural excipients offers several advantages since they are biodegradable, more eco-friendly, generally biocompatible, and safer. One of the potential products which can be extracted from CPH is pectin, which is an ingredient used in several products in the food, pharmaceutical and cosmetics industries. With the goal of optimizing the extraction parameters of pectin from CPH, the present study conducted single-factor experiments to determined three variable levels for each of the factors - ascorbic acid concentration, temperature, and solvent pH - to be used for the Box-Behnken design (BBD) -based statistical modelling. The response variables were percent yield and galacturonic acid (GA) content. From the single-factor experiments, three levels were identified for each of the factors. Initial runs of the BBD-based statistical modelling indicate that the extracted crude pectin was a high ester, low methoxy group pectin, and that it did not meet the USP requirement for GA content. It is recommended to complete the BBD-based statistical modelling phase of the study to determine the optimized extraction conditions, and to conduct more physicochemical analyses on the crude pectin extracted using such optimized conditions.